Relation between Body Iron Store and Insulin Resistance in Type 2 Diabetes (Baghdad Science Journal, 2025)
The clinical impact of interaction between body iron status (serum iron and ferritin ) and type 2 diabetes has been investigated in this study . Thirty six females were enrolled, eighteen type 2 diabetes and eighteen apparently healthy. These two groups were matched for age and body mass index BMI. The eighteen diabetes females were matched for age, BMI, pharmacological treatment (oral hypoglycemic agent), and chronic diabetes complications .The biochemical parameters measured for both groups (control and diabetes patient) were fasting insulin(Io),fasting blood glucose (Go) , serum iron and ferritin . A significant increase in all parameters in patients compared to healthy control was noticed . The insulin resistance ( IR) which was calculated by the equation:- IR= (Io µIU/ ml × Go mmol/ L)/22.5 was clearly demonstrated to be significantly higher in female diabetes patient( 275.9 ± 22.7) compared to control (41.5±11.3) .